Experimental Study on Acoustic Attenuation Due to Solid Particles. Issue 9 (2nd September 2017) - Kim, Taejin; Seo, Seonghyeon; Sung, Hong-Gye
ABSTRACT: High-frequency pressure waves present in rocket motors can be dampened by solid or liquid particles produced from their propellant combustion depending on conditions. The present study conducted an experimental investigation into the effects of particle sizes, ambient gases, and pressure wave frequencies on the attenuation of acoustic energy. Aluminum oxide powders of single-peak broad distributions with average diameters of 5.1 μm, 7.6 μm, 16.5 μm, and 36.2 μm were used to simulate condensed particles in solid rocket combustion environment. Attenuation of excited pressure waves traveling through the fixed cylindrical volume full of particle-laden helium or nitrogen gas has been measured. The number densities of particles floating in gases have been determined by use of processing of images from a high-speed camera. It is observed that alumina particles surely have attenuation effects of pressure waves. The particles in helium show approximately two times greater pressure wave attenuation than those in nitrogen, which indicates the effect of gas density on the attenuation of pressure wave by particles. The optimal particle diameter for the maximal attenuation varies with the frequency of pressure wave. Pressure wave attenuation reaches maximal values at an average particle diameter of 7.6 μm in helium and 16.5 μm in nitrogen over frequencies. Particle diameters showing maximal attenuation become shifted and so do the attenuation characteristics for both cases of helium and nitrogen for high frequency waves greater than 2500 Hz.